(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This article presents a new national program in primary grades. The positive aspects, including the importance of mother tongue and reading literacy, are discussed in terms of teaching trends, goals, and expected results based on the national curriculum. In this regard, the shortcomings and achievements are the requirements and plans.